Barusida Math Sebagai Aplikasi Media Pembelajaran Matematika Bangun Ruang Sisi Datar Berbasis Android - Wanti Rahayu; Ari Irawan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
The low level of students' understanding of the flat side space requires learning media that can support learning activities so that it is necessary to make android-based learning media. The purpose of this research is to create an application